2005
DOI: 10.1002/jcc.20269
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and topological analyses of the oxidation reaction between Mon (n = 1, 2) and N2O

Abstract: The interaction between molybdenum, atom, and dimer, with nitrous oxide has been investigated using density functional theory. The analysis of the potential energy surfaces for both reactions has revealed that a single molybdenum atom can activate the N--O bond of N2O requiring a small activation energy. However, the presence of several intersystem crossings between three different spin states, namely, septet, quintet and triplet states, seems to be the major constraint to the Mo + N2O reaction. Contrarily, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The investigators demonstrated that the NO 2 molecule adsorbs dissociatively on Pt(111), Ru(001), Ag(110), Ag(111) and Pd(111) surfaces at temperatures of about 150 K, but adsorbs molecularly on Au(111) and polycrystalline Au. The N 2 O molecule was studied theoretically with metal atoms [27][28][29] and in the reactions on fcc (111) surfaces of Rh, 30 Pt, 31 Ir 32 and Ni. 33 Nickel is an important electroactive material that displays a great adsorption ability for a molecule such as ethyne 34 relative to Rh, Pd, and Pt, and also a great catalytic ability for steam reforming.…”
Section: Introductionmentioning
confidence: 99%
“…The investigators demonstrated that the NO 2 molecule adsorbs dissociatively on Pt(111), Ru(001), Ag(110), Ag(111) and Pd(111) surfaces at temperatures of about 150 K, but adsorbs molecularly on Au(111) and polycrystalline Au. The N 2 O molecule was studied theoretically with metal atoms [27][28][29] and in the reactions on fcc (111) surfaces of Rh, 30 Pt, 31 Ir 32 and Ni. 33 Nickel is an important electroactive material that displays a great adsorption ability for a molecule such as ethyne 34 relative to Rh, Pd, and Pt, and also a great catalytic ability for steam reforming.…”
Section: Introductionmentioning
confidence: 99%
“…52,53 Additionally, localization functions have been widely used to characterize the bonding nature in transition metal complexes and thus could be an indispensable tool for their tensorial representation. [53][54][55][56][57][58][59][60] The encouraging results in the present article show incredible promise for future endeavors to tackle even more challenging problems. The existing frameworks could be further refined by leveraging recent developments in the field of computer vision.…”
Section: Discussionmentioning
confidence: 64%
“…BET [37] has been applied to different elementary reactions as proton transfers [36,58], isomerisations [59], electron transfers [60] and studies on two-state reactivity [61][62][63]. A systematic investigation of the mechanism of important organic reactions such as the Diels-Alder reactions [45,46] the 1,3-dipolar reaction between fulminic acid and acetylene [44], the molecular mechanism of the Bergman cyclization [64], the trimerization of acetylene [65] the "chameleonic vs centauric" mechanisms of the Cope rearrangement of 1,5 hexadiene and its cyano derivatives [66] the Nazarov cyclization [67] and the S N 2 reaction [68].…”
Section: Topological Analysis Of Elf and Catas-trophe Theorymentioning
confidence: 99%